Optimizing dietary lipid use to improve essential fatty acid status and reproductive performance of the modern lactating sow: a review. Issue 1 (December 2016) - Rosero, David; Boyd, R.; Odle, Jack; van Heugten, Eric
Abstract Dietary lipid supplementation benefits the prolific and high-producing modern lactating sow. A comprehensive review of recent studies showed that lipid supplementation increases average daily energy intake, which is partitioned for lactation as indicated by greater milk fat output and improved litter growth rate. Recent compelling findings showed that addition of particular lipids during lactation improved the subsequent reproductive outcome of sows. Such benefits were related to the level of dietary essential fatty acids (EFA, linoleic acid, C18:2n-6; and α-linolenic acid, C18:3n-3) during lactation. Lactation diets without supplemental EFA resulted in a pronounced negative balance (intake minus milk output) of linoleic (−25.49 g/d) and α-linolenic acid (−2.75 g/d); which compromised sow fertility (farrowing rate < 75 % and culling rates > 25 % of weaned sows). This phenomenon seems to be increasingly important with advancing sow age because of a progressive reduction of body EFA pool over successive lactations. The net effect of supplemental EFA during lactation was to create a positive EFA balance, which improved the subsequent reproduction of sows. Adequate linoleic acid intake improved the proportion of sows that farrowed in the subsequent cycle (Farrowing rate (%) = [(−1.5 × 10−3  × linoleic acid intake (g/d)2 ) + (0.53 × linoleic acid intake (g/d)) + (45.2)]; quadraticP  = 0.002, R2  = 0.997, RMSE = 0.031). In addition, increasing linoleic acid intake increased the number of pigs born in the subsequent cycle (total pigs born (n) = [(9.4 × 10−5  × linoleic acid intake (g/d)2 ) + (0.04 × linoleic acid intake (g/d)) + (10.94)]; quadraticP  = 0.002, R2  = 0.997, RMSE = 0.031). Supplemental α-linolenic acid resulted in a rapid return to estrus (sows bred: sows weaned = 94.2 %; wean-to-estrus interval = 4.0 d) and achieved a high retention of pregnancy (sows pregnant: sows bred = 98 %). Collectively, we conclude that a minimum dietary intake of 10 g/d of α-linolenic acid, simultaneous with a minimum of 125 g/d of linoleic acid should be provided to ≥ 95 % of the sows; thereby, achieving a maximum sow reproductive efficiency through multiple mechanisms that include rapid return to estrus, high maintenance of pregnancy and large subsequent litter size in mature sows, that appear to be susceptible to EFA deficiency.